Faktor-faktor yang Mempengaruhi Kejadian Stunting pada Keluarga dengan Baduta - Masmuri Masmuri; Lintang Sari; Diena Juliana; Dwin Seprian; Wulida Litaqia (Journal of Telenursing (JOTING), 2023)
This research was conducted to analyze the factors that influence the incidence of stunting in families with children in the Kapuas River area according to the characteristics of the region and its population. This research uses a descriptive research method with a cross sectional approach to study the dynamics of the correlation between factors that influence stunting using an observational, data collection or approach. The research results obtained showed that the growth history factor with the incidence of stunting obtained a significance value of 0.091>0.05, the history of giving breast milk with the incidence of stunting obtained a significance value of 0.000<0.0, the history of giving MPASI with the incidence of stunting obtained a significance value of 0.071>0.05, family history with the incidence of stunting, a significance value was obtained of 0.019<0.05, a history of infectious disease with the incidence of stunting obtained a significance value of 0.084>0.05, and the mother's psychological pattern with the incidence of stunting obtained a significance value of 0.000<0.05. In conclusion, there is a significant relationship between the history of breastfeeding, family history and the incidence of stunting, and the psychological pattern of the mother and the incidence of stunting in influencing the incidence of stunting in families with toddlers in the Kapuas River suburbs. Keywords: Stunting Baduta, Family with Baduta, Stunting